RESPONSE OF SOYBEAN PLANT TO INOCULATION OF ARBUSCULAR MYCORRHIZAE AND APPLICATION OF PHOSPHORUS FERTILIZER ON ACIDIC SOIL - Fahrizal, Ilham; Rahayu, Arifah; Rochman, Nur (JURNAL AGRONIDA, 2018)
The study was aimed at assessing the response of soybean plant (Glycine max L.) to inoculation of arbuscular mycorrhizae and application of phosphorus fertilizer on acidic soil. The study was conducted from February to June 2013. A factorial completely randomized design was used. The first factor was inoculation of mycorrizhae consisting of two levels, namely no inoculation and mycorrizhae inoculation of 10 g/plant. The second factor was the application of phosphorus fertilizer in four levels, namely 0 kg SP-36/ha, 100 kg SP-36/ha, 200 kg SP-36/ha, and 300 kg SP-36/ha. Results showed that soybean plant given no mycorrhizae of 10 g/plant had higher plant height at 3 weeks after planting (WAP) than those given no mycorrhizae. The application of phosphorus fertilizer was found to give significant effects on plant height at 4-7 WAP, number of leaves at 6 WAP, trunk diameter, root length, number of productive branches, fresh and dry weight of roots, fresh and dry weight of root nodes, age at first flowering, number of root nodes, leaf width, pod dry weight, number of one seeded pods and three seeded pods. It was also found that the interaction between inoculation of arbuscular mycorrhizae and application of phosphorus fertilizer gave significant effects on number of leaves at 7 WAP, canopy dry and fresh weight, pod fresh weight, number of two seeded pods, total plant fresh and dry weight, total dry seed weight, number of total pods, and number of seeded pods. Key words: Glycine max L., root nodes, pod dry weight, seeded pods